Efektivitas Pemberian Kompres Hangat Elektrik Dan Relaksasi Nafas Dalam terhadap Tingka Nyeri Dismenore pada Remaja SMK Nurul Islami Semarang - Bunga Mayang Sari; Agnes Isti Harjanti; Danny Putri Sulistyaningrum (Calory Journal Medical Laboratory Journal, 2023)
Menstrual pain (dysmenorrhea) is a pain that is felt during menstruation and is felt in the lower abdomen. The incidence of dysmenorrhea is still common in young women, including in SMK Nurul Islami Semarang. One way to reduce dysmenorrhea pain is with warm electric compresses and deep breathing relaxation. This study aimed to analyse the effectiveness of giving electric warm compresses and deep breathing relaxation on the level of dysmenorrhea pain in adolescents at SMK Nurul Islami Semarang. The research plan is a quasi-experimental design with a two-group pre-test-post-test design approach. The population in this study was composed of female students in grades 10 and 11. The sampling technique was purposive, and a total sample of 64 respondents was obtained. The statistical test used is the normality test using Kolmogorov-Sminonov, followed by the Wilcoxon test. This study found that giving electric warm compresses and deep breathing relaxation was more effective in reducing dysmenorrhea pain than giving electric warm compresses. This finding is based on the intervention group's score of 16.50, while the control group's value is 14.50. The results of this study recommend that it can be used as material for carrying out interventions for young women who experience menstrual pain (dysmenorrhea).